Healthy Living: Scrambling for a Variety of Foods - Linda B. Bobroff (EDIS)
Revised! FCS-8615, a 1-page illustrated handout by Linda Bobroff, is a word puzzle designed to get participants thinking about healthy foods. This version is updated with MyPyramid.gov logo. Published by the UF Department of Family Youth and Community Sciences, October 2006.